Participation or eschewal? Final-year secondary school students’ attitudes towards participation in higher education in Cameroon - Tongtong Zhao; Yuwei Xu (South African Journal of Education, 2022)
In this article we examine students’ attitudes towards participation in higher education in Cameroon and consider the role of personal and socioeconomic factors in their post-school educational trajectories. The data were drawn from a questionnaire survey of 1,860 final-year secondary school students from Yaoundé, Cameroon, as well as supplementary interviews with 16 students. The findings show that the majority of respondents indicated a preference to continue their education after the end of secondary school and participate in some form of higher education. However, contrary to previous studies that identify gender or SES segregation in higher education participation, the findings in this study suggest that the influence of SES and gender on students’ attitudes was minimised in the later stage of secondary schooling. Among the relatively minor external influences, institutional factors surpass family influence, and fathers’ influence is stronger than that of mothers, echoing the patriarchal cultural background in Cameroon. Considering the positive attitudes revealed in this study, it is suggested that more external efforts could be made to respond to students’ optimistic attitudes and smooth their transition processes. Higher education institutions should improve their capability to enrol and accommodate more students and patriarchal culture should also be challenged to boost women’s educational opportunities.